Translating stakeholder pressure into environmental sustainability-Studying HRM practices as mediating role - Muhammad, Rafiq (Archives of Business Research, 2019)
The research contributes towards the surviving exploration of Human Resource management, hereafter referred as HRM practices, depending on the instrumental estimation of the partner weight which leaves an effect on the organizations choices. This examination imagines HRM hones as an arrangement of the administration process that organizations are attempting to actualize keeping in mind the end goal to react the partner weight which influences the ecological manageability of the firms. Partners may apply weight on association's to execute HRM hones which could prompt enhance the ecological manageability. The current study addresses partner weight for the execution of HRM hones inside the organizations. The principle reason for this exploration is to control the partner's weight and to fill the holes occurred by external stakeholder pressure inside the organizations. The study examines the mediating effect of HRM practices with stakeholder pressure and environmental sustainability. This investigation depends on implementing the HRM practices and to control the stakeholder pressure within the firms. This investigation helps the managers to understand the importance of HRM hones. The collection of data is based on the primary and secondary sources. Primary sources are related to the questionnaires and secondary sources are related to the research articles. HR managers can use the result to control the stakeholders’ pressure and to improve the environmental sustainability. These findings are used to know about the variables that are creating the gap of communication and to decrease the pressure of stakeholders within the firms. It helps us to execute the new policies and norms within the firms.